Combined effects of temperature and clomazone (Gamit (R)) on oxidative stress responses and B-esterase activity of Physalaemus nattereri (Leiuperidae) and Rhinella schneideri (Bufonidae) tadpoles - Freitas, Juliane Silberschmidt [UNESP]; Felicio, Andreia Arantes [UNESP]; Teresa, Fabricio Barreto; Almeida, Eduardo Alves de (Elsevier B.V., 2017)
Temperature is an important factor influencing the toxicity of chemicals in aquatic environments. Neotropical tadpoles experience large temperature fluctuations in their habitats and many species are distributed in areas impacted by agriculture. This study evaluated the effects caused by the exposure to clomazone (Gamic) at different temperatures (28, 32 and 36 degrees C) on biochemical stress responses and esterase activities in Physalaemus nattereri and Rhinella schneideri tadpoles. Results evidenced that temperature modulates the effects of clomazone on biochemical response of tadpoles. Antioxidant enzymes, including catalase, superoxide dismutase (SOD), and glucose-6-phosphate dehydrogenase had their activities increased by clomazone in P. nattereri treated at higher temperatures. The biotransformation enzyme glutathione-S-transferase (GST) was also induced by clomazone at 32 and 36 degrees C. In R. schneideri, clomazone failed to alter antioxidant enzymes at 28 degrees C, but SOD and GST were increased by clomazone at higher temperatures after three days. All enzymes had their activities returned to the control levels after eight days in R. schneideri. Lipid peroxidation was induced in both species exposed to clomazone at 32 and 36 degrees C, but not at 28 degrees C. Acetylcholinesterase was not sensitive to clomazone and temperature, while most treatments impaired carboxylesterase activity. Integrated biomarker response (IBR) was notably induced by temperature in both species, and a synergic effect of temperature and clomazone was mostly observed after three days of exposure. These findings imply that tadpoles from tropical areas may present differential responses in their physiological mechanism linked to antioxidant defense to deal with temperature fluctuations and agrochemicals presence in their habitats. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Temperature; Pesticides; Neotropical tadpoles; Oxidative stress; Esterase